2009
DOI: 10.1111/j.1365-2141.2009.07609.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term sequential deferiprone–deferoxamine versus deferiprone alone for thalassaemia major patients: a randomized clinical trial

Abstract: SummaryA multicentre randomized open-label trial was designed to assess the effectiveness of long-term sequential deferiprone-deferoxamine (DFO-DFP) versus DFP alone to treat thalassaemia major (TM). DFP at 75 mg/kg, divided into three oral daily doses, for 4 d/week and DFO by subcutaneous infusion (8-12 h) at 50 mg/kg per day for the remaining 3 d/week was compared with DFP alone at 75 mg/kg, administered 7 d/week during a 5-year follow-up. The main outcome measures were differences between multiple observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 32 publications
3
55
2
Order By: Relevance
“…Compliance was better with DFP (89%) in comparison with DFO treatment (75%) as suggested by previous clinical trials in thalassemia major patients [25] . Moreover, a similar low compliance was observed in several shorter-term SCD clinical trials of hydroxyurea [26][27][28] and during DFX long-term safety and efficacy study [13], suggesting that disease and social factors specific to SCD patient populations may contribute substantially to low study completion rates [13].…”
Section: Discussionsupporting
confidence: 70%
“…Compliance was better with DFP (89%) in comparison with DFO treatment (75%) as suggested by previous clinical trials in thalassemia major patients [25] . Moreover, a similar low compliance was observed in several shorter-term SCD clinical trials of hydroxyurea [26][27][28] and during DFX long-term safety and efficacy study [13], suggesting that disease and social factors specific to SCD patient populations may contribute substantially to low study completion rates [13].…”
Section: Discussionsupporting
confidence: 70%
“…Deferasirox became commercially available during the trial; therefore, the patients who discontinued as a result of consent withdrawal or loss to follow-up may include subjects who left the study but continued to take deferasirox. The completion rate is similar to that observed in a 5-year prospective study of deferiprone-DFO combination therapy compared with deferiprone monotherapy 23 and higher than a 4-year prospective analysis of long-term deferiprone (in which dose-adjustments were not permitted by the study protocol), in which fewer than one-half of the enrolled patients completed the study. 24 Long-term deferasirox treatment led to a sustained reduction in the iron burden of the patients enrolled in the study.…”
mentioning
confidence: 48%
“…58 In Italy, a multicenter prospective randomized trial over 7 years in 265 patients found no deaths occurred in patients receiving DFP alone or in combination with DFO, whereas 10 deaths occurred in those receiving DFO alone. 59 Lai et al confirmed the superiority of combined therapy over DFO alone in treating established ironinduced cardiac disease. 60 In patients who tolerate combined therapy over several years, it is possible to reduce total body iron burden in TM to normal, assessed by serum ferritin and T2* measurement of cardiac and liver iron and to improve endocrine function.…”
Section: Combined Therapy: Dfo and Dfpmentioning
confidence: 77%